Tell Barri/Kahat: la campagna del 2002 - Pecorella, Paolo Emilio (9623f264-5037-4d8c-b9e1-5bcee188867e, 2005)
In the undulating plains of north-eastern Syria is the site of Tell Barri, identified with the city of Kahat. The archaeological sequence which has been brought to light stretches without interruption from the start of the third millennium up to the fourteenth century AD. This report records the results of the eighteenth excavation campaign, carried out by the group from the University of Florence and from the "Federico II" University of Naples. In Area G, the excavation of the chapel dating to the third millennium proceeded, bringing to light a palatine building that can be attributed to the Mid Assyrian King Adad-Nirari I. In Areas A and J, the Parthian, Hellenistic and Achemenidian layers were excavated up to the level of the Neo-Babylonian reoccupation of the Assyrian palace of Tukulti-Ninurta II. As regards the Parthian phase, investigation has proceeded on the Great Defensive Wall and on the large edifice in the lower city. The text, delivered for printing in July 2005, was published following the tragic death of Paolo Emilio Pecorella, which took place on 29 August in Tell Barri, in the course of the excavation campaign.